Effect and its mechanism of spatial coherence of track irregularity on dynamic responses of railway vehicles. (November 2020) - Lei, Simian; Ge, Yaojun; Li, Qi
Highlights: Reveal the effects of spatial coherence of track irregularities on vehicle dynamics. Derive the power spectral density function for vehicle excitations from track irregularities. Propose the concepts of coherence scale and critical wavelength. Abstract: A running vehicle is subjected to multiple stochastic excitations due to the irregular profiles of the wheels and rails. The combined wheel-rail irregularities on each wheel can be partly incoherent and partly coherent in reality. As a result, different assumptions for the coherence of such irregularities have been adopted in vibration and noise simulations so that vehicle-track dynamic analysis can be conducted. Less attention has been paid to the effects of these assumptions on dynamic responses of railway vehicles in a wide frequency range. The aim of this study is to theoretically investigate the effects of the spatial coherence of track irregularities on the dynamic behaviors of a two-dimensional vehicle. Two frequency-domain methods that have been verified using a time-domain method are presented first to calculate the dynamic responses of the vehicle. A new expression of the power spectral density (PSD) function of the excitations comprises an admittance coefficient, a coherence matrix, and a spatial PSD function of the track irregularities. The PSD functions of the responses of the vehicle are derived analytically. It is then illustrated that the periodic fluctuations of response spectra are caused by the spatial coherence of the excitations by introducing the concept of coherence scales. Finally, it is proved that the difference between the responses under coherent and incoherent excitations become insignificant when the wavelength of the irregularity is less than the critical wavelength.